Incidence of women submitted to post-abortion uterine cureting in the public health service (Research, Society and Development, 2021)
Uterine curettage is one of the most performed procedures in the public health system, especially in post-abortion, for the extraction of the conceptual product left in the uterine cavity. To this end, this article sought to analyze the quantity and total days of hospital stay of women who underwent uterine curettage after abortion in the Unified Health System. This is an ecological study of a basic, retrospective nature with a quantitative approach of a descriptive character, carried out through consultation with the Informatics Department of the Unified Health System (DATASUS). The number of abortions and curettages in the post-abortion period between 2017 and 2019 were observed in the municipalities of the State of Sergipe. The data obtained were reorganized and analyzed using the Excel version 2010 program, presented in tables with absolute numbers and percentages. After analyzing the data, it was noted that in the years 2017, 2018 and 2019, there were a total of 7,941 cases of uterine curettage performed in the regions of Sergipe. Of these, 3,196 women suffered spontaneous abortion and underwent this procedure, having a total of 12,362 days of hospital stay, resulting in an average expense of R$684.75. Thus, uterine curettage is the most used therapy in cases of abortions in the hospital environment. As it is a surgical procedure, it requires a longer hospital stay, implying high costs for public health.